Serve efficiency in men's volleyball - Häyrinen, M.; Lahtinen, P.; Mikkola, T.; Honkanen, P.; Paananen, A.; Blomqvist, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The importance of the serve is high in men`s international top volleyball. The players use mainly six different serve techniques: jump serve (JS), short jump serve (SJS), jump float (JF), short jump float (SJF), float (F) and short float (SF). The purpose of this study was to evaluate the efficiency of different serve techniques in men`s volleyball at three different levels: boy`s youth national teams, Finnish men`s league teams and men`s national teams. Serve efficiency was analyzed in nineteen matches. Eight were boy`s youth national team matches (G1, 1089 serves), five men`s Finnish League matches (G2, 1033 serves) and six men`s World League matches (G3, 1016 serves). A six-point assessment scale was used to evaluate the efficiency of the serves (5 = ace, 4 = no attack from the opponent team, 3 = opponent can use only high ball attack, 2 = opponent can use first tempo attack with a small risk, 1 = opponent can use all attack options, 0 = error). The serve technique distribution and the means and S.D. for serve efficiency for different serve techniques and groups were calculated. Ttest for independent samples was used for statistical analysis. Also ace-error ratios, ace, positive (proportion of level 3-5 serves) and error percentages for every serve technique were calculated. The proportions of different serve techniques for G1 were JS 42.1 %, SJS 2.7 %, JF 49.7 %, SJF 3.3 %, F 2.0 % and SF 0.2 %, for G2 53.5 %, 4.6 %, 29.6 %, 3.8 %, 7.5 % and 1.0 % and for G3 64.7 %, 4.2 %, 23.0 %, 5.5 %, 2.6 % and 0.0 %, respectively. The serve efficiency for JS was G1 1.78±1.50, G2 1.68±1.49 and G3 1.81±1.47, for SJS G1 1.72±1.28, G2 1.65±1.26 and G3 2.02±1.42, for JF G1 2.14±1.33, G2 1.85±1.10 and G3 1.85±1.04, for SJF G1 1.64±1.27, G2 1.69±1.17 and G3 1.57±1.06 and for F G1 1.73±1.20, G2 1.97±1.25 and G3 1.77±0.86. The efficiency of JF was significantly (p<0.01) higher for G1 than for G2 and G3. In G1 JF was significantly more efficient than JS (p<0.001) and SJF (p<0.05). The two highest ace-error ratios were for G1 F 1.00 and JF 0.83, for G2 F 1.33 and JF 0.47 and for G3 SJS 0.75 and JF 0.50. JS and SJS had the two highest ace percentages in every group, G1 5.7 % and 3.4 %, G2 6.7 % and 4.2 % and G3 5.3 % and 7.0 % and also the two highest error percentages, G1 23 % and 17 %, G2 26 % and 17 % and G3 22 % and 9 %. The two best positive percentages were for G1 JF 43 % and JS 35 %, for G2 F 35 % and JS 31 % and for G3 JS 36 % and SJS 33 %. JS and JF were two most used serve techniques. Nevertheless the use of different serve techniques differs between these three groups so that JS was used more and JF less when the level of the game was higher. JF was the proportionally most used and most efficient serve technique in G1. In G2 and G3 JS was the most used technique and it was also quite effective, but it had highest error percentage. So the high use of JS can be explained partly by the target to score direct points by ace serves.